Die GKSA se ‘sendingstilstand’ na 150 jaar - Ignatius W. Ferreira (In die Skriflig, 2020)
The RCSA’s ‘missional standstill’ after 150 years: While the Reformed Churches in South Africa (hereafter RCSA) is looking back gratefully over the past 150 years, it is also compelled to reflect on its disparaging existence of the past 25 years. Several RCSA Synods have for some time, been paying close attention to comprehensive deputy reports on ‘falling membership numbers’. They also have made incisive decisions on, among other things, a ‘Conversion Strategy’, and recently on a ‘Church Growth Ministry’. The same reduction in numbers that degraded the Christian church within the Western culture to a post-Christendom reality, has also been identified in the RCSA. This article looks back in history and focuses, among other things, on the spiritual legacy of the RCSA. This legacy, from the historical and theological development of post-Reformational theology, and also from the Netherlands, influenced the church life of the RCSA in Southern Africa. This reflection is essential to really understand the current challenges of the RCSA in order to refocus its future biblical response to God’s call. It is clear that the RCSA will have to reform missiologically in order to face the new post-Christendom reality of our globalising world.